Kesediaan Membayar (Willingness to Pay) Beras Organik di Kabupaten Karanganyar - Rofiah Rofiah; Susi Wuri Ani; Joko Sutrisno (Universitas Muhammadiyah Malang, 2020)
The objectives of this study were to estimate consumers willingness to pay (WTP) for organic rice in Karanganyar Regency, analyze the factors influencing consumers WTP and to find its most dominant factors. This study was carried out in Karanganyar Regency that was selected purposively with certain criteria, one of the regions that is developing intensively the organic cropping pattern, so that it is expected to increase production and consumption in Karanganyar Regency. This study was conducted on 60 consumers based on consideration that organic rice consumers in Karanganyar regency are still low. The sampling locations in this study are modern markets and organic rice agents in Karanganyar Regency. The method used in this study to estimate the value of WTP for organic rice is the Contingent Valuation Method (CVM) while to analyze the factors that influence and determine the most dominant factors is multiple linear regression analysis. The results of this study are the average value of willingness to pay for organic rice in Karanganyar Regency is IDR 15,367 per kilogram. Factors that influence the value of WTPs are income, trust, health awareness, age and environmental awareness. The factor that has a dominant influence on the value of willingness to pay for organic rice in Karanganyar Regency is income.